Heterogeneity in the cyclical sensitivity of job-to-job flows - Sandra Schaffner (Technische Universität Dortmund, Sonderforschungsbereich 475 - Komplexitätsreduktion in Multivariaten Datenstrukturen, 2009)
Although the cyclical aspects of worker reallocation are investigated in numerous studies, only scarce empirical evidence exists for Germany. Kluve, Schaffner, and Schmidt (2009) emphasize the heterogeneity of cyclical influences for different subgroups of workers, defined by age, gender and skills. This paper contributes to this literature by extending this analysis to job-to-job flows. In fact, job-to-job transitions are found to be the largest flows in the German labor market. The findings suggest that job-finding rates and job-to-job transitions are procyclical while separation rates are acyclical or even countercyclical. The empirical framework employed here allows demographic groups to vary in their cyclical sensitivity. In Germany, young workers have the highest transition rates into and out of employment and between different jobs. Additionally, these transitions are more volatile than those of medium-aged or old workers. By contrast, old workers experience low transition rates and less pronounced swings than the core group of medium-aged, medium-skilled men.
Keywords: E32; J63; J64; E24; 519; labor force; employment dynamics; worker flows; business cycle; worker heterogeneity; Job-to-Job; Arbeitsmobilität; Konjunkturelle Arbeitslosigkeit; Arbeitsmarkt; Konjunktur; Deutschland